2011
DOI: 10.3109/08820538.2011.588659
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Type Hypersensitivity in the Pathogenesis of Recurrent Herpes Stromal Keratitis

Abstract: Recurrent herpes stromal keratitis (HSK) is one of the leading causes of blindness in the developed world. Cyokines characteristic of Th1 cells (in particular IFN-γ and IL-2) have been shown to dominate in HSK in addition to mechanisms by nonspecific, antigen-independent effector cells such as neutrophils, basophils, and monocytes. More recently, the migration and maturation of dendritic cells (DC) within the corneal stroma of patients with HSK have been recognized as contributors to recurrent disease, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As a consequence, most corneal disease associated with HSV-1 infection is the result of recrudescence of a latent infection whereby virus is reactivated in the trigeminal ganglia and then returns to the cornea where it restimulates a memory immune response that was initially generated during primary infection (32,33). This immune response is characterized by an influx of CD4 and CD8 conventional T cells, neutrophils, macrophages, and NK and NKT cells (7,21,33,34). The role that each of these subsets of cells plays in corneal disease has been the subject of numerous publications (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, most corneal disease associated with HSV-1 infection is the result of recrudescence of a latent infection whereby virus is reactivated in the trigeminal ganglia and then returns to the cornea where it restimulates a memory immune response that was initially generated during primary infection (32,33). This immune response is characterized by an influx of CD4 and CD8 conventional T cells, neutrophils, macrophages, and NK and NKT cells (7,21,33,34). The role that each of these subsets of cells plays in corneal disease has been the subject of numerous publications (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, severing of latently infected TG neurons/nerve endings during excision of the host cornea is considered a sufficient stimulus to induce HSV-1 reactivation with anterograde virus transport to the graft site resulting either in direct viral damage or indirect damage due to an antigen-specific T-cell recall response. 10 12 Human clinical studies have shown HSV-1 DNA as well as virus particles in host corneas, in donor-rejected corneas, and in aqueous samples from patients with rejecting corneal grafts, 13 and has led to the common practice of antiviral prophylaxis as part of the management of HSK patients. Experimental studies in rabbits have also shown an increase in viral shedding in tear fluid after lamellar corneal grafts with some epithelial lesions but without development of HSK.…”
mentioning
confidence: 99%
“…The surgical excision of corneas also severs the corneal sensory nerves and can cause HSV-1 reactivation and recurrent infection in the transplanted cornea. Thus, the risk of transplant rejection due to recurrence of HSV-1, inflammation, and angiogenesis limits the long-term benefits of these surgical interventions [ 293 , 341 , 342 , 343 ].…”
Section: Hsk Therapeutic Strategies and Challengesmentioning
confidence: 99%